The Neural Blending of Words and Movement: Event-Related Potential Signatures of Semantic and Action Processes During Motor–Language Coupling - Garcia-Serrano, A (MIT Press Journals, 2021)
Behavioral embodied research shows that words evoking limb-specific meanings can affect responses performed with the corresponding body part. However, no study has explored this phenomenon’s neural dynamics under implicit processing conditions, let alone by disentangling its conceptual and motoric stages. Here, we examined whether the blending of hand actions and manual action verbs, relative to nonmanual action verbs and non-action verbs, modulates electrophysiological markers of semantic integration (N400) and motor-related cortical potentials during a lexical decision task. Relative to both other categories, manual action verbs involved reduced posterior N400 amplitude and greater modulations of frontal motor-related cortical potentials. Such effects overlapped in a window of ∼380–440 msec after word presentation and ∼180 msec before response execution, revealing the possible time span in which both semantic and action-related stages reach maximal convergence. These results allow refining current models of motor–language coupling while affording new insights on embodied dynamics at large. © 2021 Massachusetts Institute of Technology.